Penetration of Fosfomycin into IPEC-J2 Cells in the Presence or Absence of Deoxynivalenol - Martínez, Guadalupe (2013)
Fosfomycin (FOS) is an antibiotic used in pig farms for treatment and prevention of infections caused by resistant bacteria during the post-weaning period. Antibiotics and non-toxic concentrations of mycotoxins, such as deoxynivalenol (DON) are frequently found in the diet of animals. These compounds can establish interactions in the intestinal tract, which could affect and/or modify the penetration of FOS to enterocytes. The aim of this study was to determine the penetration of FOS into IPECJ-2 cells, a cell line derived from the small intestine of piglets, in the presence and absence of DON. The results from this study showed that there was statistically significant difference in the intracellular concentration of FOS between cells incubated with 580 mg/ml FOS and cells incubated with 580 mg/ml FOS and 1 mg/ml DON. The C max of the intracellular antibiotic in the culture plates incubated with FOS in absence of DON was 45.81 mg/ml with a t max of 4 h. When IPEC-2 cells were incubated with FOS and DON the C max was 20.06 mg/ml and the t max was 30 min. It is concluded that the non-toxic concentration of DON on IPEC-J2 cells after short-term exposure, interferes with the pharmacokinetics of the antibiotic.